The global burden of chronic kidney disease due to diabetes mellitus type 2 attributable to diet high in sugar-sweetened beverages among the elderly: a comprehensive analysis from 1990 to 2021 - Hu, Ben; Qiu, Xiaohan; Luo, Zhengbiao; Chen, Jingxiong; Feng, Jun; Hou, Linlin (Frontiers in Nutrition, 2025)
BackgroundThe consumption of sugar-sweetened beverages (SSBs) has been linked to numerous health complications, including chronic kidney disease due to type 2 diabetes mellitus (CKD-T2DM). However, the global burden of CKD-T2DM attributable to high SSB consumption among elderly populations remains poorly characterized.MethodsUsing data from the Global Burden of Disease Study 2021, we examined age-standardized mortality rates (ASMR) and disability-adjusted life year rates (ASDR) of CKD-T2DM attributable to high SSB consumption among individuals aged 60 years and older across 204 countries and territories from 1990 to 2021. We employed joinpoint regression analysis to assess temporal trends and conducted decomposition analysis to quantify the contributions of population growth, aging, and epidemiological changes to the observed burden.ResultsGlobally, the ASMR of CKD-T2DM attributable to high SSB consumption among elderly increased from 0.21 (95% UI: 0.10–0.38) per 100,000 in 1990 to 0.37 (95% UI: 0.18–0.62) per 100,000 in 2021, with an average annual percent change (AAPC) of 1.89% (95% CI: 1.47–2.31). The ASDR similarly increased from 4.5 (95% UI: 2.12–7.66) to 7.24 (95% UI: 3.49–11.69) per 100,000. We observed pronounced socioeconomic and geographical disparities, with high socio-demographic index (SDI) regions experiencing the highest burden and fastest increase. Notably, decomposition analysis revealed that population growth was the primary driver of increased burden globally, while epidemiological changes played a more dominant role in high SDI regions.ConclusionOur findings highlight a substantial and increasing burden of CKD-T2DM attributable to high SSB consumption among elderly populations globally, with distinct patterns across socioeconomic development levels. These results underscore the importance of targeted interventions to reduce SSB consumption, particularly in regions experiencing rapid increases in disease burden, as part of comprehensive strategies to address the growing challenge of diet-related kidney disease in aging populations.